ANALISIS ALOKASI DANA DESA TERHADAP KEMISKINAN DALAM PENINGKATAN PERTUMBUHAN EKONOMI DESA MEDAN SINEMBAH - Kembaren, Nurul Fadhilah Yusri; Syarvina, Wahyu; Rahmani, Nur Ahmadi Bi (COMPETITIVE, 2024)
The aim of this research is to determine the allocation of village funds to poverty in increasing the economic growth of Medan Sinembah Village. The method used in this research is descriptive qualitative with primary data sources. In this research, data was obtained from informants by direct interviews with parties who understand the distribution of Village Fund Allocations (ADD) to Medan Sinembah Village. The results of the research show that village funds are not distributed evenly, the distribution of funds is not on target, such as funds being distributed to people who have sufficient economic conditions while poor people do not receive village funds, and Village Fund Allocation (ADD) cannot increase economic growth in Medan Sinembah Village due to many other needs. The amount of funds provided by the government is not distributed properly to the people. Therefore, it can be recommended that more attention be paid to collecting data on the distribution of funds so that they are rightly targeted to the people who need them, and distribute all the funds provided by the government or at least 80% of government funds so that Medan Sinembah Village can increase economic growth with sufficient funds.